Formaldehyde Exposure And It’s Potential Health Risk In Some Beauty Salons In Kumasi Metropolis - James Kusi Appiah (KNUST, 2025)
A Thesis submitted to the Department of Chemistry, College of Science, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of MASTER OF PHILOSOPHY (ANALYTICAL CHEMISTRY)